Analysing The Views of Private School Administrators about Talent Management - Çağrı Aydın Gülbahar; Didem Koşar (Anı Publishing, 2020)
The aim of this study is to examine the private school administrators' views on talent management. 23 private high school administrators in Ankara in 2017-2018 academic year were selected by maximum diversity sampling method. Case study was used in this qualitative research. Data were collected using semi-structured interview form. Content analysis was used in the analysis of the data. Administrators mentioned student achievement, parents' expectations, the importance of competition, the use of information technologies, material and physical opportunities, school climate, the importance of corporate culture, wage policy and career opportunities. It was revealed that there were problems in the correct determination of talent, mentorship, electronic learning, orientation, performance evaluation system based on objective criteria and leadership development activities for the future. Management strategies of educational institutions can be formed with talent management approach, trainings that will improve the talent management practices of school administrators can be used, and schools can use various channels to attract talented teachers.